Analysis of the Effectiveness of Compliance Audit Implementation to Prevent Uncollectible Receivables at PT Ekspres Mandiri Gadai Tanjung Morawa - Aziz, Abdul (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Internal audit plays an important role in the performance of private companies, one of which is the company PT Ekspres Mandiri Gadai. In carrying out its business efforts, the PT Ekspres Mandiri Gadai branch office has several branches in the city of Medan, one of which is in Tanjung Morawa. The purpose of this study is to find out in detail what are the causes of bad debts every month at PT Ekspres Mandiri Gadai Tanjung Morawa Branch, to find out the obstacles faced in carrying out compliance audits of bad debts at PT Ekspres Mandiri Gadai, to find out the efforts that must be made so that compliance audits play their role effectively.... This research approach uses a descriptive approach and uses the Nvivo method. The implementation of the internal control system for bad debts applied at PT Ekspres Mandiri Gadai Tanjung Morawa Branch is quite adequate as seen from the elements of internal control. Such as the control environment, risk assessment of control activities, information, and communication, but the element of supervision is still not effective. Internal audit has carried out audit work quite well consisting of planning audits, evaluating, testing information, making audit reports, and following up on audit findings and providing recommendations on existing internal control weaknesses.